2019
DOI: 10.1039/c9ay01672d
|View full text |Cite
|
Sign up to set email alerts
|

Improved performance of near infrared excitation Raman spectroscopy using reflective thin-film gold on glass substrates for cytology samples

Abstract: Thin-film gold substrates offer improved performance and cost for NIR excitation Raman spectroscopy of biological cells when compared with CaF2. We demonstrate a 1.65 times enhancement in the signal to noise ratio with <5% of the cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…A spectrum was recorded from a prostate cancer cell line (PC3) fixed to a calcium fluoride substrate with 785 nm laser illumination and additional information on the sample preparation and system parameters may be found at Ref. [8]. Let it be noted that spectrum (b), as shown in Figure 6, is an estimation of expected collected irradiance that has been achieved by taking the average across a dataset of spectra.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A spectrum was recorded from a prostate cancer cell line (PC3) fixed to a calcium fluoride substrate with 785 nm laser illumination and additional information on the sample preparation and system parameters may be found at Ref. [8]. Let it be noted that spectrum (b), as shown in Figure 6, is an estimation of expected collected irradiance that has been achieved by taking the average across a dataset of spectra.…”
Section: Resultsmentioning
confidence: 99%
“…A spectrum was recorded from a prostate cancer cell line (PC3) fixed to a calcium fluoride substrate with 785 nm laser illumination and additional information on the sample preparation and system parameters may be found at Ref. [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glass slides (76 × 26 × 1 mm; Marienfeld GmbH & Co. KG, Lauda-Königshofen, Germany) were coated with ~100 nm thick gold and an ~10 nm titanium adhesive layer 56 , 57 . Glass slides were cleaned by ultrasonication in trichloroethylene, acetone, isopropyl alcohol, and pure water and dried by centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of substrates including aluminum coated glass, thin-lm gold coated substrate, borosilicate glass, synthetic fused silica, extra white soda lime glass and others, have been previously investigated to overcome the limitations of weak Raman SNR and high costs associated with the traditional CaF 2 substrate. 27,28,45 Stainless steel has the notable advantages of being easily accessible, robust/durable, relatively cheap and highly biocompatible. In our study, BC cells were found to easily attach, multiply and retain expected morphology with equal propensity on stainless steel compared to CaF 2 substrate (Fig.…”
Section: Papermentioning
confidence: 99%